Erector spinae plane versus paravertebral nerve blocks for postoperative analgesia after breast surgery: a randomized clinical trial. Issue 4 (21st January 2020) - Swisher, Matthew W; Wallace, Anne M; Sztain, Jacklynn F; Said, Engy T; Khatibi, Bahareh; Abanobi, Maryann; Finneran IV, John J; Gabriel, Rodney A; Abramson, Wendy; Blair, Sarah L; Hosseini, Ava; Dobke, Marek K; et al.
Abstract : Background: Paravertebral nerve blocks (PVBs) are frequently used to treat pain during and following breast surgery, but have various undesirable risks such as pneumothorax. The erector spinae plane block (ESPB) also provides perioperative breast analgesia, but is purported to be easier to administer with a favorable safety profile. However, it remains unknown if the new ESPB provides comparable analgesia as the decades-old PVB technique. Methods: Subjects undergoing unilateral or bilateral non-mastectomy breast surgery were randomized to a single-injection ESPB or PVB in a subject-blinded fashion (ropivacaine 0.5% with epinephrine; 20 mL unilateral or 16 mL/side for bilateral). We hypothesized that (1) analgesia would be non-inferior in the recovery room as measured on a Numeric Rating Scale (NRS) with ESPB, and (2) opioid consumption would be non-inferior in the operating and recovery rooms with ESPB. Results: Both pain scores and opioid consumption were higher in subjects with ESPBs (n=50) than PVBs (n=50; median NRS 3.0 vs 0; 95% CI −3.0 to 0; p=0.0011; and median morphine equivalents 2.0 vs 1.5 mg; 95% CI −1.2 to −0.1; p=0.0043). No block-related adverse events occurred in either group. Conclusions: PVBs provided superior analgesia and reduced opioid requirements following non-mastectomy breast surgery. To compare the relatively rare complications between the techniques will require a sample size 1–2 orders of magnitude greater than the current investigation; however, without a dramatic improvement in safety profile for ESPBs, it appears that PVBs are superior to ESPBs for postoperative analgesia after non-mastectomy breast surgery. Trial registration number: NCT03549234 .